2019
DOI: 10.1111/jcmm.14260
|View full text |Cite
|
Sign up to set email alerts
|

circEPSTI1 regulates ovarian cancer progression via decoying miR‐942

Abstract: Increasing studies show that circular RNAs (circRNAs) play vital roles in tumour progression. But, how circRNAs function in ovarian cancer is mostly unclear. Here, we detected the expression of circEPSTI1 in ovarian cancer and explored the function of circEPSTI1 in ovarian cancer via a series of experiments. Then, we performed luciferase assay and RNA immunoprecipitation (RIP) assay to explore the competing endogenous RNA (ceRNA) function of circEPSTI1 in ovarian cancer. qRT‐PCR verified that circEPSTI1 was ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 21 publications
0
44
0
Order By: Relevance
“…Guo et al assessed and identified circEPSTI1 as an outstanding potential diagnostic biomarker for systemic lupus erythematosus (SLE) 25 . Moreover, circEPSTI1 was found to regulate ovarian cancer progression and could be used as a biomarker and therapeutic target in ovarian cancer 26 . In our present study, we demonstrated for the first time that circEPSTI1 expression is increased in OSCC and that overexpressing or silencing circEPSTI1 can respectively promote or inhibit OSCC cell proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al assessed and identified circEPSTI1 as an outstanding potential diagnostic biomarker for systemic lupus erythematosus (SLE) 25 . Moreover, circEPSTI1 was found to regulate ovarian cancer progression and could be used as a biomarker and therapeutic target in ovarian cancer 26 . In our present study, we demonstrated for the first time that circEPSTI1 expression is increased in OSCC and that overexpressing or silencing circEPSTI1 can respectively promote or inhibit OSCC cell proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…CircEPSTI1 was remarkably upregulated in OvCa specimens compared to adjacent nontumor counterparts. In addition, circEPSTI1 was correlated with tumor size and lung metastasis in mouse xenografts, and this circRNA may potentially enhance OvCa cell proliferation and invasion and inhibit cell apoptosis in vivo [61]. Moreover, miR-942, a tumor suppressor in OvCa, was found to directly target the linear form of circEPSTI1, while circEPSTI1 was proven to sponge miR-942, suggesting a potential effect of circEPSTI1 on EPSTI1, which was downregulated in OvCa tissues [61].…”
Section: Hsa_circ_0000479mentioning
confidence: 97%
“…Recent data have proved that several circRNAs can influence the growth, survival, invasion, EMT, angiogenesis, and drug resistance in gynecological cancers. Manipulation of circRNA abundance has been shown to possess anti-tumor activities in experimental xenograft models of CC [88,91,95], OC [121,123,124] and EC [156].…”
Section: Circrnas As Potential Therapeutic Targets For Gynecological mentioning
confidence: 99%